1992
DOI: 10.1136/ard.51.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of cancer in patients with systemic lupus erythematosus.

Abstract: To evaluate the risk of cancer in patients with systemic lupus erythematosus (SLE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
138
2
6

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(157 citation statements)
references
References 12 publications
11
138
2
6
Order By: Relevance
“…Previous reports have suggested a possible role of cyclophosphamide in inducing malignant transformation (17). The present data and those reported by Petterson et a1 (9) indicate that the occurrence of NHL and other hematopoietic cancers is not related to the use of cyclophosphamide. None of the 6 patients with hematologic malignancies received cyclophosphamide and/or other cytotoxic agents before the diagnosis of cancer.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Previous reports have suggested a possible role of cyclophosphamide in inducing malignant transformation (17). The present data and those reported by Petterson et a1 (9) indicate that the occurrence of NHL and other hematopoietic cancers is not related to the use of cyclophosphamide. None of the 6 patients with hematologic malignancies received cyclophosphamide and/or other cytotoxic agents before the diagnosis of cancer.…”
Section: Discussionsupporting
confidence: 76%
“…Lewis et a1 ( 5 ) found the frequency of cancer in 484 patients with SLE to be 3.7%. Petterson et a1 (9) compared the occurrence of cancers in 205 SLE patients with that in the total Finnish population and found a 2.6-fold increased risk of all malignancies.…”
mentioning
confidence: 99%
“…504 Smedby et al 505 also reported a strong association of celiac disease with risk of T-cell NHL (SIR 5 51.0, 95% CI: 35.0-68.0), and a weaker, yet statistically significant, association with risk of B-cell NHL (SIR 5 2.2, 95% CI: 1.3-3.6). In a Finnish cohort, 4 cases of NHL were observed (0.09 expected) among women with SLE, 506 and an increased risk was reported in a multicenter casecontrol study (OR 5 8.4, 95% CI: 1.6-45.0). 507 Seven cases of NHL were observed (0.16 expected) in a follow-up study of patients with Sj€ ogren's syndrome.…”
Section: Interactions With Environment and Lifestyle Factorsmentioning
confidence: 99%
“…As with congenital immunodeficiencies, increases in NHL are seen with autoimmune conditions such as rheumatoid arthritis (Kamel et al, 1995), systemic lupus erythematosus (Pettersson et al, 1992), Sjogren's syndrome, and celiac disease (Harris et al, 1967). Although immunosuppressive drugs used in the treatment of these conditions may cause an increase in NHL incidence, evidence suggests that the persistent inflammatory activity of the autoimmune process may have a direct link with increased risk of lymphomagenesis (Jonsson et al, 1999).…”
Section: Immunosuppressionmentioning
confidence: 99%